2017
DOI: 10.3390/w9100748
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of Bank Erosion during the Period 1930–2016: Case Study—Kolubara River Basin (Serbia)

Abstract: Abstract:The fluvial process is characterized by an intense meandering riverbed. The aim of this study was to perform a reconstruction of the lateral migration of a 15 km length of an active meandering river during the period 1930-2016. River morphological changes were analyzed and quantified from cadastral maps and aerial photographs as well as by geodetic survey and GIS. Hydrological characteristics and extreme hydrological events were evaluated in relation to bank erosion rate. The rate of bank erosion was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Spatially, the damage was done at 10 out 16 sites and amongst those sites, cross vanes and double wings exhibited the greatest damage out of six different types of practices: cross vanes, rock vanes, j-hook, double wings, log vanes, and rootwads [31]. Previously, Dragićević et al [32] evaluated flood erosion rates using aerial photography on the Kolubara River, which experienced a flood wave in May 2014, and found that the land loss in 2014 was three times larger than in 2013. Comparable to that study, the average erosion rate for the control sites was five times larger during the flood in 2010 (3.05 m 2 m −1 year −1 ) compared to the time period 2001-2009 (0.57 m 2 m −1 year −1 ).…”
Section: Flood Impactmentioning
confidence: 98%
“…Spatially, the damage was done at 10 out 16 sites and amongst those sites, cross vanes and double wings exhibited the greatest damage out of six different types of practices: cross vanes, rock vanes, j-hook, double wings, log vanes, and rootwads [31]. Previously, Dragićević et al [32] evaluated flood erosion rates using aerial photography on the Kolubara River, which experienced a flood wave in May 2014, and found that the land loss in 2014 was three times larger than in 2013. Comparable to that study, the average erosion rate for the control sites was five times larger during the flood in 2010 (3.05 m 2 m −1 year −1 ) compared to the time period 2001-2009 (0.57 m 2 m −1 year −1 ).…”
Section: Flood Impactmentioning
confidence: 98%
“…Respondents agreed with the view that geography should be represented in the educational system of Serbia with more hours per week, for example talking about natural hazards, prevention, and protection against natural hazards. Geographers of Serbia dealing with science, such as Dragićević et al [52][53][54], Burić et al [55,56], Kutiel et al [57], Malinovic-Milicevic et al [58], Lukić et al [26], Milanović et al [59], and Vyklyuk et al [60], still make a scientific contribution to the study of natural disasters. Geographers, unlike other professions, look at natural hazards from the physical geographic point of view, but also in terms of monitoring the social geographic consequences.…”
Section: Geographers and Natural Hazardsmentioning
confidence: 99%
“…The research articles included in this special issue specifically targeted three areas that are key to better understanding streambank erosion and failure, namely, monitoring [8][9][10][11], modeling [12][13][14][15][16][17], and management [18][19][20][21]. As an ensemble, the articles highlight the value of monitoring campaigns to characterize the effect of external drivers (e.g., hydrologic events), the capabilities and limitations of numerical models for predicting the response of the system (e.g., stream restoration design), and the effectiveness of management practices to prevent and mitigate the impacts of streambank erosion and failure.…”
Section: Main Outcomes Of the Special Issuementioning
confidence: 99%
“…Their results highlight the impact of different types of bank vegetation on erosion rates and their implications for calculating sediment supply. Dragićević et al [9] reconstructed the lateral migration of a 15-km reach of a meandering river using 87 years of observations from cadastral maps and aerial photographs. This study is a relevant example of the use of historical data to characterize long-term trends of bank erosion relative to the hydrologic regimes that triggered them.…”
Section: Monitoringmentioning
confidence: 99%